2016
DOI: 10.1007/s10068-016-0190-8
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal activity of Azotobacter nigricans against trichothecene-producing Fusarium species associated with cereals

Abstract: Antifungal efficacy of on infection, total seedlings mass, root and shoot length, and seed germination in maize, sorghum, and wheat were investigated. Antifungal efficacy of against, , and showed a significant reduction in growth and infection incidence (up to 50%) in all the three treated cereals. However, challenge inoculation of spp. to the three cereals showed 100% infection incidence. Total mass of the maize seedlings increased two fold by treatment; however, only a slight increase was observed in sorghum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 22 publications
1
17
0
Order By: Relevance
“…Indeed, the biological approaches are increasingly explored due to their higher effectiveness and safety for humans ( Jaibangyang et al, 2020 ; Rodríguez and Núñez, 2020 ). Our probiotic candidate L. brevis MYSN105 and its CFS both reduced significantly the growth of mycotoxigenic fungi, with findings from this study are in good accordance with previous investigations ( Nagaraja et al, 2016 ; Deepthi et al, 2017 ; Plocková et al, 2018 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Indeed, the biological approaches are increasingly explored due to their higher effectiveness and safety for humans ( Jaibangyang et al, 2020 ; Rodríguez and Núñez, 2020 ). Our probiotic candidate L. brevis MYSN105 and its CFS both reduced significantly the growth of mycotoxigenic fungi, with findings from this study are in good accordance with previous investigations ( Nagaraja et al, 2016 ; Deepthi et al, 2017 ; Plocková et al, 2018 ).…”
Section: Discussionsupporting
confidence: 93%
“…Among the biocontrol agents, probiotic lactic acid bacteria (LAB) represent a potent and interesting strategy, as they are widely used in food/feed and are part of beneficial gut microbiota capable of producing antimicrobial metabolites. There are different reports of using bacteria to control mycotoxigenic Fusarium species ( Nagaraja et al, 2016 ; Deepthi et al, 2017 ). However, probiotic LAB has not been used so far to control F. verticillioides .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the species used as a probiotic starter culture may play an important role in providing health benefits to consumers and also in avoiding food spoilage due to colonization of mycotoxigenic fungi (Wei et al, 2006; Guimarães et al, 2018). These isolates can also be used in agricultural practices for controlling mycotoxigenic fungi in post- and pre-harvesting practices (Nagaraja et al, 2016; Deepa et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The experiment was conducted in a controlled environment, and the growth of F. graminearum mycelia in wheat kernels was observed in flasks containing bacterial cell-free culture supernatant. In the work of Nagaraja et al [ 52 ], zones of inhibition were observed on Petri plates where Azotobacter nigricans was cultured in the presence of several Fusarium species. According to the authors, the analyzed bacterial species can be effectively used to protect wheat, maize and sorghum against toxin-producing fungi of the genus Fusarium .…”
Section: Inhibition Of the Growth Of Fusarium Pmentioning
confidence: 99%